2022
DOI: 10.1038/s41598-022-17291-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of focused low-intensity pulsed ultrasound versus pulsed shortwave diathermy on knee osteoarthritis: a randomized comparative trial

Abstract: The aim of this study was to compare the efficacy and safety of focused low-intensity pulsed ultrasound (FLIPUS) with pulsed shortwave diathermy (PSWD) in subjects with painful knee osteoarthritis (OA). In a prospective randomized trial, 114 knee OA patients were randomly allocated to receive FLIPUS or PSWD therapy. The primary outcome was the change from baseline in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total scores. Secondary outcomes included the numerical rating scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…A certain degree of heterogeneity is evidenced in the studies regarding the types of proposed interventions. The diathermy with the highest occurrence was SWD, with 43 studies (63%) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], and MWD had the second highest occurrence with 13 articles (19%) [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. One article, Hammad 2019 [ ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A certain degree of heterogeneity is evidenced in the studies regarding the types of proposed interventions. The diathermy with the highest occurrence was SWD, with 43 studies (63%) [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], and MWD had the second highest occurrence with 13 articles (19%) [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. One article, Hammad 2019 [ ...…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven studies [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 72 , 73 , 86 , 87 , 88 ] performed the treatment in adults with osteoarthritis (OA), 26 studies concerning knee OA, and 1 study concerning a mixed population affected by knee or hip OA. Of the 27 studies, 22 used SWD, 2 MWD, 2 CRET, and 1 ‘low power radiofrequency electromagnetic radiation’ (LPRER).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Furthermore, in a prospective randomized trial, FLIPUS was more effective than pulsed shortwave diathermy in alleviating pain and in improving dysfunction and health status among subjects with knee OA in the short term. 14 In basic science studies, FLIPUS application promoted ECM production in a surgically induced OA rabbit model by downregulating prostaglandin E2 and nitric oxide, joint effusion volume, and chondrocyte apoptosis. 15 Meanwhile, electron microscopy analysis showed that FLIPUS induced typical autophagosomes that enclosed mitochondria in degenerative chondrocyte, which indicated that FLIPUS potentially inhibits the apoptosis via mitophagy activation.…”
Section: Introductionmentioning
confidence: 99%